“Green” nZVI-Biochar as Fenton Catalyst: Perspective of Closing-the-Loop in Wastewater Treatment - Anita Leovac Maćerak; Aleksandra Kulić Mandić; Vesna Pešić; Dragana Tomašević Pilipović; Milena Bečelić-Tomin; Djurdja Kerkez (Molecules, 2023)
In the framework of wastewater treatment plants, sewage sludge can be directed to biochar production, which when coupled with an external iron source has the potential to be used as a carbon–iron composite material for treating various organic pollutants in advanced oxidation processes. In this research, “green” synthesized nano zero-valent iron (nZVI) supported on sewage sludge-based biochar (BC)–nZVI-BC was used in the Fenton process for the degradation of the recalcitrant organic molecule. In this way, the circular economy principles were supported within wastewater treatment with immediate loop closing; unlike previous papers, where only the water treatment was assessed, the authors proposed a new approach to wastewater treatment, combining solutions for both water and sludge. The following phases were implemented: synthesis and characterization of nano zero-valent iron supported on sewage sludge-based biochar (nZVI-BC); optimization of organic pollutant removal (Reactive Blue 4 as the model pollutant) by nZVI-BC in the Fenton process, using a Definitive Screening Design (DSD) model; reuse of the obtained Fenton sludge, as an additional catalytic material, under previously optimized conditions; and assessment of the exhausted Fenton sludge’s ability to be used as a source of nutrients. nZVI-BC was used in the Fenton treatment for the degradation of Reactive Blue 4—a model substance containing a complex and stable anthraquinone structure. The DSD model proposes a high dye-removal efficiency of 95.02% under the following optimal conditions: [RB4] = 50 mg/L, [nZVI] = 200 mg/L, [H2O2] = 10 mM. pH correction was not performed (pH = 3.2). Afterwards, the remaining Fenton sludge, which was thermally treated (named FStreated), was applied as a heterogeneous catalyst under the same optimal conditions with a near-complete organic molecule degradation (99.56% ± 0.15). It could be clearly noticed that the cumulative amount of released nutrients significantly increased with the number of leaching experiments. The highest cumulative amounts of released K, Ca, Mg, Na, and P were therefore observed at the fifth leaching cycle (6.40, 1.66, 1.12, 0.62, 0.48 and 58.2 mg/g, respectively). According to the nutrient release and toxic metal content, FStreated proved to be viable for agricultural applications; these findings illustrated that the “green” synthesis of nZVI-BC not only provides innovative and efficient Fenton catalysts, but also constitutes a novel approach for the utilization of sewage sludge, supporting overall process sustainability.